ANTROPOLOGI: KAJIAN TERHADAP EVOLUSI HINGGA MENJADI ALAT PENGKAJI AGAMA ISLAM - Jannataini , Zahira; Kambali, Kambali (CV. Adiba Aisha Amira, 2023)
Religious studies cannot be understood using a normative theological approach, but need to use new approaches that are in line with developments in thought, social dynamics and even developments in science and technology. This research is included in qualitative research with the type of library research which is carried out based on a detailed study of various scientific papers, including research results in the form of research articles and books. This research aims to examine the history of anthropology from its inception until it can be used as a tool to study Islamic religion. The result is that anthropology, as a science that studies humans, becomes very important for understanding religion. Anthropology studies humans and their behavior to understand differences in human culture. Equipped with a holistic approach and anthropology's commitment to understanding humans, anthropology is actually an important science for studying religion and its social interactions with various cultures.